Attentional focus practices and its effects on elite ten-pin bowling performance - Tiara Atiqah Mohammad Hanafee (Nanyang Technological University, 2021)
Attentional focus consists of two dimensions, external and internal. Various studies have concluded that external foci have a positive effect on performance and accuracy for sports involving discrete skills. Little is known on the effects of attentional focus on ratings of perceived exertion (RPE). This study aims to understand the attentional focus strategies implemented by varsity tenpin bowlers in Singapore, and to study the effects of different strategies on tenpin bowling performance and accuracy. A descriptive study using the Attentional Focus Preference Questionnaire (AFPQ) was conducted on 38 university tenpin bowlers. Subsequently, 15 volunteers were gathered to participate in a within-subject experiment studying the effects of external and internal instructions conditions on tenpin bowling performance, accuracy, and mental and physical RPE. The AFPQ revealed task-relevant external cues as the most frequently used strategy, followed closely by task-relevant thoughts. The experiment concluded no significant differences across external, internal, and control conditions for performance (p=0.612), accuracy (p=0.875), mental RPE (p=0.891), and physical RPE (p=0.727). Performance and accuracy were greatest under control conditions, followed by external and internal. It is theorized that a combination of external and internal cues is essential for improved performance and accuracy in tenpin bowling, Further research on the effects of developing a personalized bowling routine could be studied.